Biomarkers ST2 and interleukin 33 for assessing the severity of cardiac inflammation and fibrosis in patients with chronic heart failure - O. M. Drapkina; A. V. Kontsevaya; A. Ya. Kravchenko; A. V. Budnevskiy; R. E. Tokmachev; T. A. Chernik (Российский кардиологический журнал, 2021)
Chronic heart failure (CHF) is a pathology that affects more than 37 million people worldwide. Despite the introduction of new drugs into practice, that have proven their effectiveness in the treatment of patients with CHF, the life expectancy of these patients is growing at a slow pace. At the same time, the insufficient effect of neurohormonal blockers for the treatment of patients with CHF with preserved ejection fraction (CHFpEF), which prevails in the general structure of CHF, indicates a significant role of unidentified pathological processes in the development of this form of the disease. In recent years, the role of cardiac fibrosis has been actively studied within the framework of the investigation of the pathogenesis of CHFpEF, the probable biomarkers of which are interleukin (IL) 33 and suppression of tumorigenicity 2 (ST2). This literature review examines the influence of the IL-33/ ST2 interaction as a biomarker of cardiac fibrosis on the course of CHF and the possibilities of its practical application.